2017
DOI: 10.1159/000480066
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Minimally Invasive Surfactant Therapy in Preterm Infants at 29-32 Weeks Gestation

Abstract: Background: Most preterm infants born at 29-32 weeks gestation now avoid intubation in early life, and thus lack the usual conduit through which exogenous surfactant is given if needed. Objective: The aim of this work was to examine whether a technique of minimally invasive surfactant therapy used selectively at 29-32 weeks gestation would improve outcomes. Methods: We studied the impact of selective administration of surfactant (poractant alfa 100-200 mg/kg) by thin catheter in infants with respiratory distre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 24 publications
4
63
0
Order By: Relevance
“…MIST also showed a slightly impaired surfactant distribution in the lungs compared with surfactant via endotracheal intubation 22. In line with our results, Dargaville repeatedly discussed the possible dose–effect relation on MIST success 1 23. He observed 100% MIST success in all preterm infants who received a 200 mg/kg dose of surfactant 1.…”
Section: Discussionsupporting
confidence: 88%
“…MIST also showed a slightly impaired surfactant distribution in the lungs compared with surfactant via endotracheal intubation 22. In line with our results, Dargaville repeatedly discussed the possible dose–effect relation on MIST success 1 23. He observed 100% MIST success in all preterm infants who received a 200 mg/kg dose of surfactant 1.…”
Section: Discussionsupporting
confidence: 88%
“…However, endotracheal intubation has harmful effects including, bradycardia and hypotension in infants . Newer minimally invasive strategies for surfactant therapy have been reported and provide an intriguing option to manage RDS . These techniques incorporate the utilization of a small catheter placed in the trachea to administer surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly half of the preterm babies (<34 weeks) with respiratory distress syndrome (RDS) managed on continuous positive airway pressure (CPAP) require surfactant administration via endotracheal tube intubation. 1 However, endotracheal intubation has harmful effects including, bradycardia and hypotension in infants. 2 Newer minimally invasive strategies for surfactant therapy have been reported and provide an intriguing option to manage RDS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, Dargaville et al 27) showed that the incidence of pneumothorax reduced from 8.0% to 2.4% after introducing…”
Section: Discussionmentioning
confidence: 99%